Effect of ethanol, dry extract and reducing sugars on density and viscosity of Brazilian red wines - Neto, Flavia S. P. P. [UNESP]; Castilhos, Mauricio B. M. de [UNESP]; Telis, Vania R. N. [UNESP]; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2015)
BACKGROUND Density and viscosity are properties that exert great influence on the body of wines. The present work aimed to evaluate the influence of the alcoholic content, dry extract, and reducing sugar content on density and viscosity of commercial dry red wines at different temperatures. The rheological assays were carried out on a controlled stress rheometer, using concentric cylinder geometry at seven temperatures (2, 8, 14, 16, 18, 20 and 26 degrees C).RESULTSWine viscosity decreased with increasing temperature and density was directly related to the wine alcohol content, whereas viscosity was closely linked to the dry extract. Reducing sugars did not influence viscosity or density. Wines produced from Italian grapes were presented as full-bodied with higher values for density and viscosity, which was linked to the higher alcohol content and dry extract, respectively.CONCLUSIONThe results highlighted the major effects of certain physicochemical properties on the physical properties of wines, which in turn is important for guiding sensory assessments. (c) 2014 Society of Chemical Industry
Keywords: Red dry wine; Rheology; Physicochemical properties; Physical properties; Principal component analysis